The replication of the human respiratory syncytial virus in a T cell line has multiple ineffective steps - De Souza Cardoso, Ricardo; Ana Carolina Lunardello Coelho; Bruna Laís Santos De Jesus; Vitti, Brenda Cristina; Juliano De Paula Souza; Mendes Viana, Rosa Maria; Pontelli, Marjorie C; Murakami, Tomoyuki; Armando Moraes Ventura; Ono, Akira; Arruda, Eurico (bioRxiv, 2020)
Abstract Human respiratory syncytial virus is the most frequent cause of severe respiratory disease in children. The main targets of HRSV infection are epithelial cells of the respiratory tract and the great majority of the studies regarding HRSV infection are done in respiratory cells. Recently, the interest on respiratory virus infection of lymphoid cells has been growing, but details of the interaction of HRSV with lymphoid cells remain unknown. Therefore, this study was done to assess the relationship of HRSV with A3.01 cells, a CD4+ T cell line. We found by flow cytometry and fluorescent focus assay that A3.01 cells are susceptible but virtually not permissive to HRSV infection. De-quenching experiments revealed that the fusion process of HRSV in A3.01 cells is reduced in comparison to HEp-2 cells, an epithelial cell lineage. Quantification of viral RNA by qPCR determined that the replication of HRSV in A3.01 cells was modest. Western blot and quantitative flow cytometry analyses demonstrated that the production of HRSV proteins in A3.01 was significantly lower than in HEp-2 cells. Additionally, we found by fluorescence in situ hybridization that the inclusion body-associated granules (IBAG’s) are almost absent in HRSV inclusion bodies in A3.01 cells. We also assessed the intracellular trafficking of HRSV proteins and found that HRSV proteins co-localized partially with the secretory pathway in A3.01 cells, but these HRSV proteins and viral filaments are present only scarcely at the plasma membrane. HRSV infection of A3.01 CD4+ T cells is virtually unproductive as compared to HEp-2 cells, with virion production hampered by low fusion, hypofunctional inclusion bodies, altered trafficking of viral proteins to the plasma membrane.